Taking stock of the relationship between gang membership and offending: a meta-analysis - Pyrooz, David C. (Criminal justice and behavior, 2016)
This study takes stock of empirical research examining the relationship between gang membership and offending by subjecting this large body of work to a meta-analysis. Multilevel modeling is used to determine the overall mean effect size of this relationship based on 1,649 effect size estimates drawn from 179 empirical studies and 107 independent data sets. The findings indicate that there is a fairly strong relationship between gang membership and offending (Mz = .227, confidence interval [CI] = [.198, .253]). Bivariate and multivariate moderator analyses not only reveal that this relationship is robust across the vast majority of methodological variations but also show that the gang membership?offending link is stronger when studying active gang members, and weaker in prospective research designs, non-U.S. samples, and when controlling for theoretical confounders and mediators. These results affirm the efforts of researchers, policymakers, and practitioners to understand and respond to gang behaviors, and are used to identify aspects of this literature that are most worthy of continued attention.